Thermodynamic analysis and comparison for different direct-heated supercritical CO2 Brayton cycles integrated into a solar thermal power tower system. (1st December 2017) - Zhu, Han-Hui; Wang, Kun; He, Ya-Ling
Abstract: In this paper, a complete mathematical model is developed to carry out the thermodynamic analysis and comparison for different direct-heated S-CO2 Brayton cycles (simple, pre-compression, recompression, partial-cooling, and intercooling) integrated into a solar power tower (SPT) system. Based on the model, the effect of turbine inlet temperature (TIT) on the thermodynamic performances of the receiver, the thermal energy storage unit, the S-CO2 power cycle blocks and the integrated SPT systems is investigated respectively for these cycles. Additionally, a comparison of cycle efficiencies and overall integrated SPT system efficiencies is performed for five S-CO2 cycles at a series of total recuperator conductance ( UA total ) values. The results reveal that the TIT exhibits a parabolic effect on the overall efficiencies for each S-CO2 cycle, and the intercooling S-CO2 cycle achieves the highest overall efficiencies followed by the recompression, the partial-cooling, the pre-compression, and the simple cycles at different TIT values. Furthermore, the partial-cooling cycle possesses the highest overall specific work at each TIT and offers higher overall efficiencies than the recompression cycle at a constant TIT (650 °C) as the UA total is rather low, having the potential to reduce the costs of integrated SPT systems with limited UA total values. Highlights: The integration of five different direct-heated S-CO2 Brayton cycles into a solar power tower system is studied. A complete mathematical model is developed for the direct integrated SPT systems. A comprehensive thermodynamic analysis and comparison are carried out among five S-CO2 Brayton cycles. The effect of UA total on the cycle efficiencies and overall system efficiencies is investigated.